HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR DASAR-DASAR GAMBAR TEKNIK SISWA PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 BANGKINANG - 534-542 , Putri Andayani (CIVED, 2014)
ABSTRACT This research is based on the lack of learning motivation and learning outcomes on principles mechanical drawing subject which is under minimum completeness criteria for students of year of school 2011-2012 construction drawing program in SMKN 1 Bangkinang. Research hypothesis that expressed is there is a relationship between learning motivation and learning outcomes on principles drawing subject for students of year of school 2011-2012 construction drawing program in SMKN 1 Bangkinang. This research is descriptive correlation with simple random sampling of 45 students and research subject is students of year of school 2011-2012 construction drawing program. Research data were gathered by questionnaire with Likert-scale, and X variable was learning motivation and Y variable was student’s learning outcomes. Analysis was conducted in three stages: (1) data description, (2) pre-analysis testing, and (3) research data hypothetical testing. Research data was analyzed with SPSS v.20. From data analysis, it is acquired correlation coefficient (r) of 0.301 and signification from correlation value is 0.044 which less than 0.05. It means that there is a relationship between learning motivation and learning outcomes on principles mechanical drawing subject in SMKN 1 Bangkinang. Keyword: learning motivation, learning outcomes, principles mechanical drawing.